Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013): The Xth International Conference, April 23-26, 2013, Tomsk, Russia; [proceedings]; Advanced Materials Research : Advanced materials, synthesis, development and application (2014, 2014)
Title screen